Two Approaches to Nonprofit Financial Ratios and the Implications for Managerial Incentives. (June 2015) - Eckerd, Adam
Nonprofits compete in donation markets for resources and are expected to report on the financial stewardship of the organization. Without a clear comparative signal to differentiate organizations in this resource market, simple financial ratios have been used as proxy measures of relative organizational efficiency. Two conceptual models can be applied to the use of these ratios: first, as dichotomous conformance thresholds that identify poor performers who are unable to meet some minimum standard, or second, as directly comparable scales of performance where more optimized ratios can be used to distinguish the best performers. These two different conceptual models imply two different managerial approaches and potential organizational outcomes. This research assesses the extent to which nonprofits that are evaluated by an external evaluator appear to use the ratios as thresholds to pass or as scales to optimize.